NF‐κB factors control the induction of NFATc1 in B lymphocytes. Issue 11 (26th September 2014) - Muhammad, Khalid; Alrefai, Hani; Marienfeld, Ralf; Pham, Duong Anh Thuy; Murti, Krisna; Patra, Amiya K.; Avots, Andris; Bukur, Valesca; Sahin, Ugur; Kondo, Eisaku; Klein‐Hessling, Stefan; Serfling, Edgar
<x xml:space="preserve">Abstract</x> In peripheral lymphocytes, the transcription factors (TFs) NF‐κB, NFAT, and AP‐1 are the prime targets of signals that emerge from immune receptors. Upon activation, these TFs induce gene networks that orchestrate the growth, expansion, and effector function of peripheral lymphocytes. NFAT and NF‐κB factors share several properties, such as a similar mode of induction and architecture in their DNA‐binding domain, and there is a subgroup of κB‐like DNA promoter motifs that are bound by both types of TFs. However, unlike NFAT and AP‐1 factors that interact and collaborate in binding to DNA, NFAT, and NF‐κB seem neither to interact nor to collaborate. We show here that NF‐κB1/p50 and c‐Rel, the most prominent NF‐κB proteins in BCR‐induced splenic B cells, control the induction of NFATc1/αA, a prominent short NFATc1 isoform. In part, this is mediated through two composite κB/NFAT‐binding sites in the inducible Nfatc1 P1 promoter that directs the induction of NFATc1/αA by BCR signals. In concert with coreceptor signals that induce NF‐κB factors, BCR signaling induces a persistent generation of NFATc1/αA. These data suggest a tight connection between NFATc1 and NF‐κB induction in B lymphocytes contributing to the effector function of peripheral B cells.